A qualitative investigation of stress related to studying architecture at degree level in the UK. (February 2021) - Xie, Yarong; Yaqoob, Anum; Mansell, Warren; Tai, Sara
Architecture students have been reported to experience significant stress, yet little has been researched. This study aims to examine how architecture students experience and cope with stress. Twelve participants studying Architecture at bachelors and masters levels took part in individual interviews. Interviews were transcribed verbatim and analysed using thematic analysis. Three over-arching themes emerged: sources of stress in architecture studies, effects of stress and coping with stress. Participants reported of experiencing stress due to heavy and constant workloads, accepting the culture of working hard, subjective aesthetics, tutors and their critique. Stress experiences differed for year 1 and year 3 undergraduates. Students reported feelings of demotivation as a result. Many participants reported time management and making use of the supportive network of tutors and peers as coping strategies. Some participants acknowledged that things get better with time and the reward from producing a piece of work helped them to restore their motivation.